2013
DOI: 10.1590/s1516-635x2013000400008
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different dietary concentrations of Amino Acids on the performance of two different Broiler Strains

Abstract: Four Nutritional Programs (NP) used in the Brazilian poultry industry were tested in two broiler strains (Cobb 500 and Ross 308). NP varied in the concentrations of their main essential amino acids (AA) and were classified as Low, Regular, High and Mixed (high AA concentrations up to 21 days and regular concentrations after that). Minimum digestible Met+Cys/Lys, Thr/Lys, Arg/Lys, Ile/Lys, and Val/Lys ratios were 0.74, 0.64, 1.05, 0.65 and 0.75, respectively, in all NP, and no minimum amount of CP was fixed. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 25 publications
(26 reference statements)
0
16
1
1
Order By: Relevance
“…Moreover, the significant difference that was observed with regards to main effect of energy in terms average daily gain, feed conversion ratio and cost/kg gain at finisher phase of wet season and the nonsignificant difference in feed intake, water intake and mortality across all the three energy levels, is similar to the findings of Zahid and Hussain (2002), which showed significant difference (P<0.05) in the feed conversion ratio of boiler birds fed different energy and protein concentration, however, the values they reported were lower than those observed in the present study. This is because the concentration of the nutrients used in the two separate study differs and also the environmental temperature, but Ebling et al (2013) reported nonsignificant difference in the feed conversion ratio of boiler birds fed different amino acid levels which disagrees with findings of this study. As the case with the previous phases of the experiment, the birds that consumed high energy diet had the highest cost of production compared to those fed low and medium energy diets, From this result it can be said that; since the birds that consumed low and medium energy diets performed better in terms of weight gain, than those that consumed high energy diet which also had a better feed conversion ratio than those that consumed high energy diet, yet they had the same feed intake and mortality.…”
Section: Performance Parameters Of Different Broiler Strains At Finiscontrasting
confidence: 99%
“…Moreover, the significant difference that was observed with regards to main effect of energy in terms average daily gain, feed conversion ratio and cost/kg gain at finisher phase of wet season and the nonsignificant difference in feed intake, water intake and mortality across all the three energy levels, is similar to the findings of Zahid and Hussain (2002), which showed significant difference (P<0.05) in the feed conversion ratio of boiler birds fed different energy and protein concentration, however, the values they reported were lower than those observed in the present study. This is because the concentration of the nutrients used in the two separate study differs and also the environmental temperature, but Ebling et al (2013) reported nonsignificant difference in the feed conversion ratio of boiler birds fed different amino acid levels which disagrees with findings of this study. As the case with the previous phases of the experiment, the birds that consumed high energy diet had the highest cost of production compared to those fed low and medium energy diets, From this result it can be said that; since the birds that consumed low and medium energy diets performed better in terms of weight gain, than those that consumed high energy diet which also had a better feed conversion ratio than those that consumed high energy diet, yet they had the same feed intake and mortality.…”
Section: Performance Parameters Of Different Broiler Strains At Finiscontrasting
confidence: 99%
“…For the total rearing period (1 to 42 days), although the production efficiency index was similar between strains, lower feed intake and better feed conversion ratio were obtained in Cobb ® broilers compared with Ross ® birds (p<0.05). On the other hand, Ebling et al (2013) observed that Ross ® broilers were heavier on the first day and during the entire rearing period, but presented higher feed intake and worse feed conversion ratio when compared with Cobb ® broilers. Mustafa et al (2014), studying the effect of the addition of acetic acid at 1% and 2% to the drinking water, reported significant increases in body weight and body weight gain, and better feed conversion ratio on day 42 days in the both Ross ® and Cobb ® broilers when compared with control.…”
Section: Resultsmentioning
confidence: 92%
“…Feed-to-poultry N efficiency was calculated from Ebling et al (2013) for a broiler reaching 3.65 kg live weight in 47 days with a feed conversion ratio of 1.67 and a crude protein content of 20.8 % in feed. Egg production was included in the feed-to-poultry N efficiency.…”
Section: Review Of Potential N Efficienciesmentioning
confidence: 99%